One-punch man. 05 - ONE, 1986- (VIZ Media, 2016)
"Nothing about Saitama passes the eyeball test when it comes to superheroes, from his lifeless expression to his bald head to his unimpressive physique. However, this average-looking guy has a not-so-average problem-he just can't seem to find an opponent strong enough to take on! To stop a Demon-level crisis, Saitama and company head toward the action. However, even Class S heroes prove to be no match for the Deep Sea King! In order to protect the good citizens, our heroes will need to summon all of their courage and confront this threat!"--Amazon.